Ameliorating effect of glutathione‐enriched herbal formulation (glothione) on alloxan‐induced experimental diabetic model by modulating oxidative stress and pathogenesis. Issue 4 (6th February 2020) - Sreevallabhan, Sheethal; Mohanan, Ratheesh; Sukumaran, Sandya; Sobha, Anumol Parayil; Jose, Svenia Periyappurathu; Sukumarapillai, Asha; Jagmag, Tariq; Tilwani, Jayesh
Abstract: Diabetes Mellitus is a common metabolic or endocrine disorder that occurs as a result of insufficient amounts of insulin secretion or defect in the action of insulin produced from pancreatic beta cells. Antioxidant containing food items are very effective in reducing complications that arise due to diabetes, indicating that it may be beneficial for treating metabolic disorders. In this study, we used some essential nutrients enriched with glutathione, named as Glothione (GN), and evaluated the antidiabetic effect of GN in alloxan‐induced diabetic rats. The treatment with GN showed significant reduction in the blood glucose level, HbA1c level, and liver markers like SGOT, SGPT, and ALP and shows increased antioxidant status and decreased inflammatory markers. Histopathological analysis of pancreas and liver tissue showed that there were no abnormalities in the rat after the administration of GN. Thus, antioxidant‐enriched formulation of GN can be used as a potent hypoglycaemic drug. Practical applications: Glothione is a glutathione‐enriched formulation that contains essential nutrients required for the normal functioning of the body. Recent trends in lifestyle and food habits have been noted to cause health risks and subject the body through physical and physiological stress––hence the importance of antioxidant‐rich foods. Antioxidants are capable of boosting metabolism and other physiological processes. Thus, the consumption of GN can enhance the antioxidant status within the body. GN does not contain any chemical ingredients so it will not cause any side effects. It has a strong antidiabetic effect and is also able to control a number of diseases. Abstract : During diabetic condition free radical formation was very high due to high oxidative stress developed in the body which was ultimately lead to the tissue damage. But the glutathione enriched formulation Glothione supplementation significantly blocked the ROS generation thereby it helps to inhibit the lipid peroxidation and Inflammatory markers. As a result, glothione administration helps to maintain the normal architecture of liver and pancreatic tissues.